Organisational justice and smoking: the Finnish Public Sector Study - Kouvonen, Anne; Vahtera, Jussi; Elovainio, Marko; Cox, Sara J; Cox, Tom; Linna, Anne; Virtanen, Marianna; Kivimaki, Mika (BMJ Publishing Group, 2007)
Study Objective: To examine the extent to which justice of decision-making procedures and interpersonal relations is associated with smoking. Setting: Ten municipalities and 21 hospitals in Finland. Design and Participants: Cross-sectional data derived from the Finnish Public Sector Study were analysed with logistic regression analysis models with generalized estimating equations. Analyses of smoking status were based on 34 021 employees. Separate models for heavy smoking (>20 cigarettes per day) were calculated for 6295 current smokers. Main results: After adjustment for age, education, socio-economic position, marital status, job contract, and negative affectivity, smokers who reported low procedural justice were about 1.4 times more likely to smoke >20 cigarettes per day compared with their counterparts with high justice. In a similar way, after adjustments, low justice in interpersonal treatment was significantly associated with an elevated prevalence of heavy smoking (odds ratio (OR) = 1.35, 95% CI = 1.03 to 1.77 for men and OR = 1.41, 95% CI = 1.09 to 1.83 for women). Further adjustment for job strain and effort-reward imbalance had little effect on these results. There were no associations between justice components and smoking status or ex-smoking. Conclusions: The extent to which employees are treated with justice in the workplace seems to be associated with smoking intensity independently of established stressors at work.